Investigation of the Inflationary Process of the Theory of JBD - Teryan, H. K.; Kotanjyan, A. S.; Harutunyan, G. H.
The cosmological model is considered in the presence of a conformally coupled field in the evolution of the early Universe. Such a field, satisfying the condition of general covariance, leads to the appearance of an additional term in the functional of the action, which connects the scalar field with scalar curvature, which can apparently serve as an analogue of the potential energy of a scalar field. Such a variant of action arises in the Jordan-Bruns-Dicke theory as a result of the well-known conformal transformations of Bekenstein. The problem can be represented as an autonomous dynamical system, and qualitative methods can be used to analyze such a system.
Keywords: Physics